1998
DOI: 10.1046/j.1365-2850.1998.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Managed mental health care: problems and possibilities

Abstract: Case management has become an established organizational approach to mental health care. However, a recent development of case management, known as 'managed care' has received only limited attention in the UK and this has been confined to acute medical or surgical hospital care. The potential of managed care as applied to mental health care is uncertain. This paper clarifies the nature of managed care and discusses its relevance to mental health care, in particular to the care of people suffering from schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…The changes to the study ward were unpredictable and proved devastating to the overall goal of implementing the care pathway. However, the complex nature of schizophrenia may also complicate the procedure of implementation given the diversity of views regarding its care and treatment ( Jones & Norman 1998). However, the implementation of a care pathway may work towards a more integrated service which values collaborative working and a more responsive and inclusive relationship with the user.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes to the study ward were unpredictable and proved devastating to the overall goal of implementing the care pathway. However, the complex nature of schizophrenia may also complicate the procedure of implementation given the diversity of views regarding its care and treatment ( Jones & Norman 1998). However, the implementation of a care pathway may work towards a more integrated service which values collaborative working and a more responsive and inclusive relationship with the user.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of recording and analysing variances is to be able to instigate remedial action to ensure the patient meets oncoming outcomes and secondly, to improve on future care pathways ( Schriefer 1995). This latter function is usually performed in quality audit meetings ( Jones & Norman 1998). There have been many reported advantages of the care pathway system, such as reduced length of stay (LOS) and costs of care, although most studies focus on medical/surgical conditions ( Zehr et al .…”
Section: What Are Care Pathways?mentioning
confidence: 99%
See 1 more Smart Citation
“…These are the types of problems that are faced by users of mental health services. It has been suggested that as so little is known about the course and outcomes of serious mental illness, and as treatment tends to be so individual, it would be difficult to develop pathways in the area (Jones & Norman 1998). Empirical research and evaluation concerning care pathways in mental health is limited (Jones 2003).…”
Section: Background To Care Pathwaysmentioning
confidence: 99%
“…The variety of differing meanings ascribed to the term 'case management' has resulted in confusion regarding its practice and definition (Jones, 1998). Community case management has its origins within the post-Second World War healthcare reforms of the USA (Jones, 1998). It is recognized as being a systematic approach to service delivery, ensuring adequate support for those discharged from institutional care (Stein & Test, 1980).…”
Section: Case Management Practices In Community Mental Health Nursingmentioning
confidence: 99%